1999
DOI: 10.1097/00001888-199906000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences and correlates of ethnic harassment in the U.S. Women Physiciansʼ Health Study

Abstract: The prevalences of ethnic harassment at various stages of medical training and practice are high, and not decreasing. This has serious potential ramifications for the medical profession's goal of a diverse physician workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 0 publications
2
43
2
Order By: Relevance
“…Despite recent efforts to foster racial/ethnic diversity within the physician workforce, a majority of non-Hispanic black physicians reported experiencing discrimination in their cur- These findings are similar to those from national surveys conducted more than a decade ago, 1,2 suggesting that significant numbers of non-majority physicians continue to experience discrimination at work. However, the experience of perceived discrimination does not appear to be static over the career course of individual physicians.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Despite recent efforts to foster racial/ethnic diversity within the physician workforce, a majority of non-Hispanic black physicians reported experiencing discrimination in their cur- These findings are similar to those from national surveys conducted more than a decade ago, 1,2 suggesting that significant numbers of non-majority physicians continue to experience discrimination at work. However, the experience of perceived discrimination does not appear to be static over the career course of individual physicians.…”
Section: Discussionsupporting
confidence: 52%
“…1 Another national study, conducted in 1993-1994 among female physicians, found that approximately 60% of non-majority respondents reported racial/ethnic discrimination at work. 2 Further, physicians from non-majority backgrounds are generally less satisfied with their careers 1,3 and less likely to be promoted than their majority colleagues with similar academic productivity. 4,5 Since the 1990s, however, achieving racial/ethnic diversity within the physician workforce has been a national priority.…”
Section: Introductionmentioning
confidence: 99%
“…Prior qualitative studies of racial/ethnic minority high school students, medical students, residents, and practicing physicians described their perceptions and experiences of discrimination within healthcare organizations 4,15,24,25 . Surveys of practicing physicians found that racial/ethnic discriminatory experiences extend postmedical training for significant numbers of racial/ethnic minority physicians 1,2,6,7 . We extended the previous work with practicing physicians of African descent 4 by characterizing the challenges and potential consequences that may arise as healthcare organizations respond to recommendations for open dialogue about race.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Physicians of African descent report discrimination at work, 1,2,4,7,8 and experiencing perceived racerelated discrimination in the workplace can negatively affect job satisfaction and career trajectories. 4 Furthermore, research with physicians of African descent has suggested that negative racerelated experiences are often ignored or normalized, 4,8 limiting potentially beneficial discussions about improving the quality of work life for physicians in the healthcare workplace.…”
mentioning
confidence: 99%
“…Occupational stereotyping was demonstrated by Leong and Hayes (1990), who showed respondents thought Asian Americans were more likely to be successful as computer scientists, engineers, and mathematicians and less likely to be successful as insurance sales people. Occupational discrimination has also been documented against Asian American scientists and engineers within U.S. universities (National Science Foundation, 2004) and against women physicians (Corbie-Smith, Frank, Nickens, & Elon, 1999).…”
Section: Asian American Career Developmentmentioning
confidence: 99%